Role of brassinosteroids in fruit trees with emphasis on abiotic stress conditions: A review (2022)
Climate change can cause stress events in crops, mainly due to changes in precipitation and temperature. Among the crops that are affected are fruit trees, a group of species of great importance due to their nutritional value in the human diet. These species can be affected by abiotic stress conditions due to changes in water availability, temperature and radiation. For this reason, different alternatives have been generated that could mitigate this affectation, such as the exogenous application of brassinosteroids (BR). BR play an important role in the growth and development of plants, it is also involved in the response of plants to abiotic stress through the regulation of solute concentration, stomatal opening, protection of the photosynthetic apparatus and the increase of the antioxidant capacity, mainly. This review article aims to synthesize the role of BR in the growth and development of fruit trees, as well as the role they play in the response to abiotic stress conditions, gene expression, and hormonal balance.